2023
DOI: 10.3390/w15162867
|View full text |Cite
|
Sign up to set email alerts
|

Scour Development Around an Oblong Bridge Pier: A Numerical and Experimental Study

Abstract: The complex flow structure around bridge piers is challenging for both experimental and numerical studies. Therefore, investigating the capabilities of Computational Fluid Dynamics (CFD) tools in resolving the flow structure and the mechanism of sediment entrainment into and out of the scour hole remains a challenging task. In this study, the scour depth around an oblong bridge pier and the bed shear stress distributions in time and space were numerically investigated using the Computational Fluid Dynamics (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…It is evident that nearly all the data points collapse to the perfect line, falling within the ±20% error range. The previous relevant studies [36,37] reported an average error of approximately 3% in their simulated scour results. Our results indicate a relatively larger average error of around 9%.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 91%
“…It is evident that nearly all the data points collapse to the perfect line, falling within the ±20% error range. The previous relevant studies [36,37] reported an average error of approximately 3% in their simulated scour results. Our results indicate a relatively larger average error of around 9%.…”
Section: Comparison With Experimental Resultsmentioning
confidence: 91%
“…Ettema et al [28] presented a contemporary approach to scour-depth estimation, combining semiempirical formulation, advanced experimentation, and computational fluid dynamics (CFD), reflecting on the evolution of understanding complex pier flow fields over the past six decades and suggesting areas for further research to enhance design estimation of scour depth. Bento et al [29] numerically investigated the complex flow structure and sediment entrainment mechanisms around an oblong bridge pier using the Sediment Simulation in Intakes with Multiblock option (SSIIM) computational fluid dynamics (CFD) tool, aiming to accurately reproduce measured scour depths with an average relative error of less than 3%.…”
Section: Introductionmentioning
confidence: 99%